2017
DOI: 10.1128/aac.00302-17
|View full text |Cite
|
Sign up to set email alerts
|

Community Composition Determines Activity of Antibiotics against Multispecies Biofilms

Abstract: In young cystic fibrosis (CF) patients, is typically the most prevalent organism, while in adults, is the major pathogen. More recently, it was observed that also plays an important role in exacerbations of respiratory symptoms. These species are often coisolated from CF lungs, yet little is known about whether antibiotic killing of one species is influenced by the presence of others. In the present study, we compared the activities of various antibiotics against, , and when grown in monospecies biofilms with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 57 publications
(46 reference statements)
1
27
0
1
Order By: Relevance
“…Furthermore, using an in vivo burn wound co-infection model of P. aeruginosa and S. aureus, RADLINSKI et al [66] found that the antibiotic-potentiating effect of LasA dominates over the antibiotic-antagonising effect of HQNO, resulting in a net increased susceptibility of S. aureus in the presence of P. aeruginosa. These data are in agreement with recent findings by TAVERNIER et al [49], who reported a decreased tolerance of S. aureus to different antibiotic classes when grown in a multispecies biofilm with P. aeruginosa and S. anginosus. Co-culturing of S. aureus with these two CF community members prevented vancomycin-induced thickening of the cell wall (a protective mechanism during antibiotic exposure), which might be explained by the production of LasA by P. aeruginosa [66].…”
Section: Through Alterations Of the Cell Wallsupporting
confidence: 94%
See 2 more Smart Citations
“…Furthermore, using an in vivo burn wound co-infection model of P. aeruginosa and S. aureus, RADLINSKI et al [66] found that the antibiotic-potentiating effect of LasA dominates over the antibiotic-antagonising effect of HQNO, resulting in a net increased susceptibility of S. aureus in the presence of P. aeruginosa. These data are in agreement with recent findings by TAVERNIER et al [49], who reported a decreased tolerance of S. aureus to different antibiotic classes when grown in a multispecies biofilm with P. aeruginosa and S. anginosus. Co-culturing of S. aureus with these two CF community members prevented vancomycin-induced thickening of the cell wall (a protective mechanism during antibiotic exposure), which might be explained by the production of LasA by P. aeruginosa [66].…”
Section: Through Alterations Of the Cell Wallsupporting
confidence: 94%
“…The enhanced tolerance of S. anginosus to vancomycin was due to an increased cell wall thickness, as a result of co-culturing with these CF pathogens [50]. Furthermore, it was found that soluble factors produced by S. aureus were mediating the enhanced antibiotic tolerance in the described multispecies community, in a strain-independent manner [49]. Another example of antibiotic protection through alterations of cell wall components was described by TOGNON et al [51].…”
Section: Through Alterations Of the Cell Wallmentioning
confidence: 95%
See 1 more Smart Citation
“…Due to this reduced mucociliary clearance, bacteria colonize the lungs of patients with CF and establish chronic, polymicrobial infections that cause increased inflammation and respiratory function decline (2). Recent studies have demonstrated that the microbiota in the lungs form polymicrobial biofilms, and that mixed bacterial biofilm populations can affect antibiotic tolerance and bacterial virulence (3, 4).…”
Section: Introductionmentioning
confidence: 99%
“…decline (2). Recent studies have demonstrated that the microbiota in the lungs form polymicrobial biofilms and that mixed bacterial biofilm populations can affect antibiotic tolerance and bacterial virulence (3,65).…”
mentioning
confidence: 99%